Evaluation of sugarcane for animal feed in the Baixada Fluminense – RJ - Augusto Brandão de Carvalho, Carlos (Revista Ciência Agronômica, 2021)
The edaphoclimatic adaptation of sugarcane varieties and clones can ensure higher forage productivity for animal feed. Anexperiment was conducted at the Seropédica campus of the Federal Rural University of Rio de Janeiro for the evaluation of two varieties(RB867515 and RB969017) and two clones (RB058046 and RB098022) of sugarcane under a randomized block design with seven replications.Biometric variables, tillers m-1, leaf area index (LAI), Brix degree, maturation index (MI), as well as forage and total yields, were evaluatedduring the cultivation of the sugarcane-plant cycle. Sugarcanes were planted on 10/08/2018 and harvested on 09/13/2019, totaling 323 daysafter planting (DAP). The data were analyzed using the R software, under randomized blocks and repeated measurements in time for biometricvariables, tillers m-1, LAI, Brix Degree and MI. Means were compared using the Tukey test (p < 0.10). Clone RB098022 presented 20.2% moretillers m-1 than both the other varieties. At 296 DAP, both clones and the variety RB969017 presented MI higher than 0.85, indicating them as anearlier cycle than the variety RB867515 (MI = 0.91 to 323 DAP). Higher and similar forage and total yields were obtained with clone RB098022and variety RB867515 (means 141.6 and 151.2 Mg ha-1, respectively). All sugarcanes adapted to edaphoclimatic conditions during plant canecultivation, and it is recommended to use the clone RB098022 and the variety RB867515 for animal feed in the Baixada Fluminense region.